2020
DOI: 10.1136/neurintsurg-2020-016299
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation of acute ischemic strokes during the COVID-19 crisis

Abstract: BackgroundThe COVID-19 pandemic has disrupted established care paths worldwide. Patient awareness of the pandemic and executive limitations imposed on public life have changed the perception of when to seek care for acute conditions in some cases. We sought to study whether there is a delay in presentation for acute ischemic stroke patients in the first month of the pandemic in the US.MethodsThe interval between last-known-well (LKW) time and presentation of 710 consecutive patients presenting with acute ische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
124
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 16 publications
14
124
1
1
Order By: Relevance
“…There was also no significant difference in NIHSS score between March 2019 and March 2020 (p=0.8173). This was consistent with Schirmer et al who reported no change in NIH score from 2019 [ 9 ]. Finally, the patient outcomes as measured by mRS were similar between March and April 2019 and March and April of 2020 (p=0.49) (Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was also no significant difference in NIHSS score between March 2019 and March 2020 (p=0.8173). This was consistent with Schirmer et al who reported no change in NIH score from 2019 [ 9 ]. Finally, the patient outcomes as measured by mRS were similar between March and April 2019 and March and April of 2020 (p=0.49) (Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…A delay in management of stroke patients may be related to the COVID-19 pandemic. Schirmer et al compared stroke severity and time to presentation between patients who presented with stroke in the pre-COVID and intra-COVID period at twelve institutions, and the corresponding months from one year prior [ 9 ]. There was a significant increase in time interval between symptom onset and time to presentation to a stroke center.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for a number of reasons including fear of contagion or severe illness complications due to COVID-19 infection, a number of patients with acute cerebrovascular diseases remained home, losing the possibility of being correctly treated. This phenomenon was similarly observed in a number of countries [35,38,[56][57][58]. Last, the outpatient assistance of stroke survivors was also highly reduced or stopped.…”
Section: Discussionmentioning
confidence: 61%
“…and the Endovascular Neurosurgery Research Group published data demonstrating that patients had a significantly longer last known well to time of presentation interval during the COVID-era. 10 This finding has been corroborated by several institutions and groups across the world. 8 A recent study from a single center in New Jersey, one of the most heavily COVID-impacted states in the country, corroborated the decrease in overall stroke volume but also found a greater proportion of patients with stroke presenting with LVOs during the COVID-19 period.…”
Section: Where Have All the Strokes Gone?mentioning
confidence: 71%